Analyzing the 22‐item Sino‐Nasal Outcome Test using item response theory. Issue 9 (9th June 2016) - Crump, R. Trafford; Liu, Guiping; Janjua, Arif; Sutherland, Jason M.
Abstract : Background: The 22‐item Sino‐Nasal Outcome Test (SNOT‐22) is a widely applied patient‐reported outcome instrument used to assess the severity of symptoms associated with chronic rhinosinusitis. The purpose of this study was to evaluate the measurement performance of the SNOT‐22 instrument on an item‐level basis, in a sample of patients awaiting elective surgery for chronic rhinosinusitis. Methods: This study involved secondary analysis of SNOT‐22 data that was prospectively collected from patients diagnosed with chronic rhinosinusitis and awaiting endoscopic sinus surgery in Vancouver, Canada. This study used classic test theory and a 2‐parameter graded‐response model to evaluate the SNOT‐22 items' abilities to measure the severity of chronic rhinosinusitis in terms of patients' self‐reported symptoms. This approach models each item's discriminability and difficulty, which provides insight into how well they respectively measure symptoms related to chronic rhinosinusitis. Results: Factor analyses indicated that there are 5 domains of measurement in the SNOT‐22. The majority of items demonstrated strong discriminability between symptom severities. Likewise, most of the items demonstrated strong difficulty measuring the symptoms across their range of levels. The exception was those items related to psychological symptoms. Differential item functioning demonstrated that very few of the SNOT‐22 items were answered significantly differently by gender or age subgroups. Conclusion: This item‐level analysis demonstrates that, in general, the SNOT‐22 is a strong instrument. Items related to psychological symptoms require further investigation and warrant a supplemental patient‐reported outcome instrument.